Barreiras na captação de recursos: um estudo a respeito das barreiras de investimento para o investidor em instituições financeiras de pequeno e médio portes - Angelin, Flávio Antônio (2008)
This paper s aim is to unearth the barriers raised by individual investors when facing the decision to invest their resources with small and medium sized banks. A thorough sampling amongst potential investors followed by an in depth analysis of the effective barriers which inhibit them when deciding to invest in the financial markets, was undertaken. To substantiate the results obtained, suppositions utilized by the potential investors, as arguments for theoretical barriers against investing with small and medium sized banks. The sampling data analysis shows that the first barrier is the non-acquaintance from the investors about small and medium sized banks, caused by the lack of information about these, contributing to the low credibility perception. Both the results obtained through the studies added to the suppositions voiced by the potential investors, can serve as help in formulating the aforementioned banks marketing studies and strategies, serving also to implement actions towards increasing their clientele by the elimination of said barriers. As a corollary more resources will be originated in order to generate a sustainable growth in their loan portfolios